Ancient views on what is music - Whitwell, David (Texas Whitwell publishing, 2013)
This book follows the fascinating attempt of man to explain the nature of Music, that powerful and mysterious art from which cannot be seen. From original accounts from the earliest period of writing when Music was associated with the gods to the early Christian Church, which tried to explain that Music is the part of mathematics you can hear, the speculation continued. Eventually man began to realize that he is more than Reason, that he has a experiential side as well and this led to writing of understanding vs feeling, the bicameral mind finally explained by modern clinical brain research. Music is finally understood as a special language of feeling.